Genotypic and phenotypic characterization of resistance to fenhexamid, carboxin, and, prochloraz, in Botrytis cinerea isolates collected from cut roses in Colombia - Giraldo, Diego; Saldarriaga, Catalina; García, Héctor; López, Miguel; González, Adriana (Frontiers in Microbiology, 2024)
Gray mold, caused by Botrytis sp., is a significant disease in ColombianColombian rose crops. I and its control depends primarily on the intensive use of chemically synthesized fungicides. Despite the importance of this pathogen, there are is limited information in Colombian floriculture about molecular taxonomy of species, the genetic and fungicide resistance of populations and their genetic mechanism of resistance in Colombian floriculture. In this study, we analyze 12 isolates of this fungus collected from rose-producing crops in the Department of Cundinamarca and. We conducted phylogenetic analysis using HSP60, G3PDH, and RPB2 gene sequences. Additionally. A phylogenetic characterization was realized using the sequences of the HSP60, G3PDH, and RPB2 genes, we realize and phenotypic -and genotypic characterization of resistance to the fungicides Fenhexamidfenhexamid, Carboxincarboxin, and Prochlorazprochloraz, based onevaluating the in vitro EC50 and presence of mutations of their target genes of each isolate. All isolates were characterized as Botrytis cinerea in the phylogenetic analysis and presents different levels of fungicide resistance to each fungicide. These levels are related to mutations in target genes were identified, with predominancy of L195F and L400F in the ERG27 gene to fenhexamid resistance, H272R/Y in the SDHB gene for carboxin resistance, and Y136F in the CYP51 gene being predominant for resistance to Fenhexamidfenhexamid, Carboxincarboxin andfor Prochlorazprochloraz resistancerespectively. AdditionallyFinally, these mutations were not related to morphological changes. Collectively, this knowledge, presented for the first time to the Colombian floriculture, contribute to a better understanding of the genetic diversity and population of B. cinerea from rose-producing crops in the department of Cundinamarca, and serve as a valuable tool for making informed decisions regarding disease management, future research, and improving crop management and sustainability in the Colombian floriculture industry.Collectively, these findings, presented for the first time to the Colombian floriculture, contribute to a better understanding of the genetic diversity and population of B. cinerea from rose-producing crops in the department of Cundinamarca.